A multi-disciplinary approach to alternative training methods for endurance athletes and their relationship with performance - Ni Cheilleachair, N. (Limerick: University of Limerick, 2013)
The physiological determinants most closely associated with successful endurance performance are factors primarily related to oxygen uptake including V?O02max, economy of movement and lactate threshold. As a consequence, endurance athletes typically spend extended periods of training utilising modalities designed to improve aerobic capacity. Despite this, successful endurance performance in sports such as rowing requires not only a high aerobic capacity but also muscular strength and anaerobic power necessary for attacking, pace changing and final sprints. Through a multi-disciplinary approach, the aim of this research was to investigate the impact of alternative methods of training on welltrained endurance athletes in order to maximise training adaptations of the key biomechanical and physiological determinants associated with endurance performance. The effect of maximal stretch shortening cycle (SSC) fatigue on the biomechanical performance of both well-trained endurance and strength trained athletes was investigated. Maximal SSC fatigue had an immediate, debilitating effect on the performance of subsequent SSC activities for both strength and endurance athletes. This effect was realised through reductions in performance outcome and the biomechanical performance of the jump indicating that the effectiveness of the SSC was significantly reduced resulting in a decrease in performance. During recovery an enhancement above baseline values was observed for both groups of athletes. This enhancement may be attributable to a post activation potentiation (PAP) effect, leading to an acute improvement in performance as a result of prior muscle activation, whereby subsequent SSC activities can be performed with a more effective SSC. To successfully prescribe training for well-trained endurance athletes an in-depth knowledge of the specific demands of the sport is pertinent and therefore the physiological determinants of 2000 m rowing ergometer performance were also investigated. The main finding was that WV?O2max was the strongest correlate of performance and was the variable with the most influence on performance. It has been suggested that in well-trained athletes, additional increases in aerobic training may not result in any further improvement in endurance performance or associated physiological variables and therefore the effect of high intensity interval training (HIIT) on well-trained rowers was investigated. The results revealed that eight weeks of HIIT performed at 100% peak power output was a more effective means than traditional, long, slow distance training to elicit improvements in ?V?O2max and power output associated with lactate threshold. HIIT also resulted in a significant improvement in 2000 m time trial improvement, although this improvement was not significantly greater than that observed with traditional training. In summary, the findings of this thesis indicate that well-trained endurance athletes have the potential to elicit a similar PAP effect to that observed in strength trained athletes following maximal SSC fatigue. HIIT was also identified as an effective modality to optimise the development of aerobic characteristics and enhance rowing performance. In conclusion, this research adds to the existing body of research by showing that, compared to traditional training modalities adopted, alternative training methods such as maximal SSC activities and HIIT may further enhance biomechanical and physiological function and performance in well-training endurance athletes.